KEPEMIMPINAN BERKELANJUTAN DALAM MENGHADAPI TANTANGAN PENDIDIKAN DI ERA DIGITAL - Lorensia Patodingan; Julfani; Fransiska Meilani; Resti; Intan Purnamasari (CV. ADIBA AISHA AMIRA, 2024)
The digital era has brought significant transformations to the education system, introducing new challenges such as the digital divide, curriculum changes, and the need for technological skills. Sustainable leadership, which focuses on long-term strategies and continuous adaptation, is considered key to addressing these challenges and ensuring optimal educational quality. This study examines the role of sustainable leadership in tackling educational challenges in the digital era. Using a literature review method, the research analyzes theories of sustainable leadership and best practices within the digital education context. Findings from this study indicate that educational leaders who apply sustainability principles can enhance teaching effectiveness, support staff professional development, and create inclusive and responsive learning environments that address digital needs. This research provides insights into how visionary and sustainable leadership can contribute to achieving better educational outcomes and better preparation for students in the future. Recommendations for educational leaders include developing policies that support technology integration, providing ongoing staff training, and creating learning environments that foster long-term growth.